2017
DOI: 10.1259/bjr.20150472
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion CT in acute stroke: effectiveness of automatically-generated colour maps

Abstract: We demonstrated how pCT provides good diagnostic accuracy in the identification of acute ischaemic lesions. The limits of identification of the lesions mainly lie at the pons level and in the basal ganglia area. Qualitative analysis has proven to be more efficient in identification of perfusion lesions in comparison with software-generated maps. However, software-generated maps have proven to be very useful in the emergency setting. Advances in knowledge: The use of CT perfusion is requested in increasingly mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…As expected, CBF resulted more specific than MTT for stroke because MTT values can be prolonged in transitory ischaemic attack as well as stroke [19]. As previously described in literature, we found that qualitatively evaluated MTT and Tmax 1 had low specificity for perfusion deficits [12].…”
Section: Mtt and Tmaxsupporting
confidence: 81%
See 3 more Smart Citations
“…As expected, CBF resulted more specific than MTT for stroke because MTT values can be prolonged in transitory ischaemic attack as well as stroke [19]. As previously described in literature, we found that qualitatively evaluated MTT and Tmax 1 had low specificity for perfusion deficits [12].…”
Section: Mtt and Tmaxsupporting
confidence: 81%
“…Brain imaging plays a key role in the evaluation of patients suspected of ischaemic stroke allowing to reach a confident diagnosis of infratentorial stroke [ 5 , 12 ]. MRI with DWI represents the diagnostic gold standard for the detection of ischaemic lesions in the PC territories [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The penumbra always surrounds the infarct area (core), where brain tissue is irreversibly affected by ischaemic lesions. Therefore, it is crucial to quickly diagnose the condition using advanced tools of medical imaging, which make it possible not only to visualise the ischaemic region, but also to differentiate the area into the penumbral zone and the core, which is essential for adopting a treatment strategy [3,5]. In clinical practice, CTP also improves diagnostic confidence and is a useful adjunct to clinical assessment and standard imaging [5,6].…”
Section: Introductionmentioning
confidence: 99%